Clinical usefulness of inside stents in anastomotic biliary strictures after liver transplantation - Naotaka Kugiyama; Shunpei Hashigo; Katsuya Nagaoka; Takehisa Watanabe; Shinya Ushijima; Yukiko Uramoto; Motohiro Yoshinari; Jun Morinaga; Ryosuke Gushima; Masakuni Tateyama; Motohiko Tanaka; Hideaki Naoe; et al. (DEN Open)
Abstract Background Endoscopic biliary stenting is a standard treatment for biliary strictures after liver transplantation. Plastic stents are often replaced before stent dysfunction to prevent the development of cholangitis and jaundice. Therefore, the precise duration of stent patency is unclear. Methods We compared retrospectively the stent patency period and stent dysfunction rate between inside stents (IS) and conventional plastic stents (PS) in 48 patients with post‐transplant strictures, distinguishing endoscopic biliary stenting with and without stent dysfunction at stent replacement. Results In observations focused on the first treatment, the median patency periods were 369 days for IS (n = 18) and 154 days for PS (n = 30; p = 0.01), significantly longer for IS. The 1‐year cholangitis incidence rate was lower for IS (20% vs. 43%, p = 0.04). Additionally, no stent dislocation was observed for IS, but this occurred for 33.3% of PS (p = 0.004). Comparing all endoscopic biliary stenting, including second and subsequent procedures, IS again had a longer patency period than PS (356 days, n = 89, vs. 196 days, n = 127, p = 0.009). Conclusions IS had a significantly longer patency period than PS, suggesting that IS replacement could be reduced to once per year for patients who prefer less frequent stent replacement.